2023
DOI: 10.1007/s11012-023-01639-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the closed-loop controller of a discontinuous capsule drive using a neural network

Abstract: In this paper the construction of a neural-network based closed-loop control of a discontinuous capsule drive is analyzed. The foundation of the designed controller is an optimized open-loop control function. A neural network is used to determine the dependence between the output of the open-loop controller and the state of the system. Robustness of the neural controller with respect to variation of parameters of the controlled system is analyzed and compared with the original optimized open-loop control. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…the thrust bearing of the above-pressure beam (Figure 1). Such application of load to spring friction set of model 18 -578 trolley is connected with feature of design of elastically -roller slides with polymer damper with limitation of roller from falling out (Figure 4) [15,16]. At the same time, the spring-friction set of the trolley is located on the side of the external rail thread.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the thrust bearing of the above-pressure beam (Figure 1). Such application of load to spring friction set of model 18 -578 trolley is connected with feature of design of elastically -roller slides with polymer damper with limitation of roller from falling out (Figure 4) [15,16]. At the same time, the spring-friction set of the trolley is located on the side of the external rail thread.…”
Section: Resultsmentioning
confidence: 99%
“…F , i.e. symmetrical application of external load relative to longitudinal axis of symmetry of above-pressure beam, as in bogie of model 18-100 [14,15]. Elastic forces of sets of springs 62…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an experimental study of the vibro-impact self-propulsion technique was reported, as shown in figure 4(b), where a mathematical model was developed for studying the dynamical characteristics of the capsule robot in the nonsmoothed multibody system [35][36][37]. In addition, a closed-loop control system for the capsule robots based on the neural network was proposed, which improved the continuity and stability of motion by establishing the relationship between the controller and the system state through machine learning [38]. Until now, many optimization methods have been carried out to improve the structural models and dynamic models of the capsule robots, but some complex factors such as the surface viscosity, surface wrinkling, and intestinal motility have not been deeply studied, which limits the applications of these models in the actual environments.…”
Section: Locomotion Of Capsule Robotsmentioning
confidence: 99%